The Effectiveness of Law Enforcement in Securing Vehicle Assets by Finance Companies Based on Law Number 42 of 1999 concerning Fiduciary Guarantees - Dian Noviyani; Dadan Taufik Fathurohman (Al-Makki Publisher, 2026)
The expansion of Indonesia’s financing sector has increased the provision of vehicle loans, with fiduciary guarantees serving as a legal instrument to protect creditors against debtor default. However, asset recovery practices often involve legal issues, such as unprocedural vehicle repossessions and the involvement of unqualified debt collectors. This research aimed to assess the effectiveness of law enforcement in protecting vehicle assets by financing companies based on Law Number 42 of 1999 concerning Fiduciary Guarantees, as well as to analyze the extent of legal protection provided to debtors. This empirical juridical (socio-legal) research combined legal and sociological approaches by using direct observation and literature studies, with qualitative data analysis. The findings indicated that Law Number 42 of 1999 provides a legal basis for financing companies to execute fiduciary guarantee objects when debtors fail to fulfill their obligations. However, the implementation of this law remained suboptimal due to several obstacles, including unregistered fiduciary guarantees, the absence of fiduciary guarantee certificates, inadequate legal understanding among the parties involved, and challenges in the vehicle repossession process. Furthermore, the Constitutional Court Decision Number 18/PUU-XVII/2019 established that the execution of fiduciary guarantees should not be conducted unilaterally without an agreement regarding the occurrence of default (wanprestasi) or a final and binding court decision. Therefore, strengthening compliance with legal provisions, improving supervision, and enhancing legal awareness are necessary to achieve legal certainty and equitable protection for both creditors and debtors.